2017
DOI: 10.1002/eqe.2867
|View full text |Cite
|
Sign up to set email alerts
|

Modified seismic design of concentrically braced frames considering flexural demand on columns

Abstract: Summary Special concentrically braced frames (SCBFs) are considered as one of the most economical and effective lateral force‐resisting systems in structures located in the regions of high seismicity. Steel braces in a braced frame undergo large axial deformations in tension and compression to dissipate the seismic energy. However, past studies have shown that SCBFs exhibit the soft‐story hinge mechanisms and unpredictable failure patterns under earthquake loading conditions. These inelastic responses along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Nine cyclic loading steps are applied until a maximum brace deformation corresponding to a story drift of 5%. This limiting value of story drift has been fixed considering the maximum inter‐story drift noted in SCBFs under the seismic loading and the probable connection failure beyond this drift level …”
Section: Numerical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Nine cyclic loading steps are applied until a maximum brace deformation corresponding to a story drift of 5%. This limiting value of story drift has been fixed considering the maximum inter‐story drift noted in SCBFs under the seismic loading and the probable connection failure beyond this drift level …”
Section: Numerical Studymentioning
confidence: 99%
“…This limiting value of story drift has been fixed considering the maximum inter-story drift noted in SCBFs under the seismic loading 37 and the probable connection failure beyond this drift level. 38…”
Section: Imposed Displacement Historymentioning
confidence: 99%
“…suggest that the design axial forces in columns should be evaluated assuming that braces have yielded at all storeys, whereas Bosco et al 15 . and Kumar et al 16 . point out that the design procedures reported in seismic codes or in literature generally neglect or significantly underestimate the bending moments of columns.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of previous experimental tests and numerical studies indicating that a limited yielding beam is not detrimental to nonlinear response, 10 a different approach with yielding beams is suggested by Tan et al 11 Several research studies have also proved that the rules for the application of the capacity design principles are often not effective in preventing yielding or buckling of the columns of the braced frame. 7,[12][13][14][15][16] In this regard, Longo et al 12 suggest that the design axial forces in columns should be evaluated assuming that braces have yielded at all storeys, whereas Bosco et al 15 and Kumar et al 16 point out that the design procedures reported in seismic codes or in literature generally neglect or significantly underestimate the bending moments of columns. Indeed, these bending moments are negligible when braces are elastic, but they can be significant when braces are in their inelastic range of behaviour and damage concentrates at a few storeys.…”
Section: Introductionmentioning
confidence: 99%
“…Because pin connection performance in actual structures closely resembles that of rigid connections, it can be assumed that the additional demand in the connections will be transferred to the columns as well. Kumar, et al, (2017) performed dynamic analysis in Perform-3D to study the seismic response of steel braced frames and they consequently proposed a new design approach taking into account the flexural demand on columns. They proposed three different limit states (P1 through P3) for braced-frame design, but it seems difficult to utilize this design approach in practice.…”
Section: Analytical Studies On Scbfsmentioning
confidence: 99%